Studi Literatur: Obesitas sebagai Faktor Resiko terhadap Kejadian Urolitiasis secara Klinis - Hasnawati Hasnawati; Elsa Trinovita; Yudi Y Ambeng (Jurnal Surya Medika (JSM), 2021)
The incidence of urolithiasis tends to relapse, causing increased mortality and medical costs. In 2015, there were 22.1 million cases of urolithiasis which caused death in about 16,000 people. Obesity is a risk factor that can increase the incidence of urolithiasis. However, there are differences in the results of studies regarding the relationship between obesity and urolithiasis. This literature review aims to analyze the factors that influence the relationship between obesity and urolithiasis. This literature review study uses a systematic review design. The data source used in this literature review is secondary data in scientific journals that have met the inclusion and exclusion criteria. Based on data synthesis from the fifteen journals studied, twelve journals stated a relationship between obesity and the incidence of urolithiasis. In contrast, the other three stated that there was no relationship between obesity and the incidence of urolithiasis. Obesity is associated with a spectrum of metabolic disorders that lead to increased excretion of urinary lithogenic factors. In addition, obesity can increase urolithiasis in types of calcium oxalate and uric acid stones.